Upaya Kepala Madrasah Dalam Meningkatkan Mutu Kegiatan Belajar Mengajar di MAS Al Ulum Bantan Tengah Kecamatan Bantan Bengkalis Riau Tahun Ajaran 2023/2024 - Muhamad Anwar (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research aims to describe the efforts of the Head of MAS AL ULUM Bantan Tengah in improving the quality of teaching and learning activities at MAS AL ULUM Bantan tengah which consists of The concept of the head of the madrasah, The efforts of the head of the madrasah in improving the quality of teaching and learning, and The quality of education. This research uses descriptive qualitative research methods. The informants in this research were the Principal, Head of the Library and Library Employees. The key informant in this research is a library employee because he is directly involved in the library at MAS AL ULUM Bantan tengah. Data collection techniques use observation, interviews and documentation studies. Test the validity of the data by increasing diligence in research and using reference materials. The results of the research also show that the Madrasah Head's efforts to improve the quality of teaching and learning activities at MAS AL ULUM Bantan tengah have supporting factors and inhibiting factors in improving the quality of teaching and learning activities, among the supporting factors in trying to improve the quality of teaching and learning activities such as the head of the madrasah always focusing on his work , There is solid and unified cooperation between school principals, teachers and employees, while inhibiting factors include: There are still teachers who lack discipline, such as arriving late to school, late entering class, relatively minimal education operational funds. From the efforts made by the school principal, it can be concluded that the principal of MAS AL ULUM Bantan tengah always strives to improve the quality of teaching and learning.